2017
DOI: 10.1097/sla.0000000000001814
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial to Evaluate Splenectomy in Total Gastrectomy for Proximal Gastric Carcinoma

Abstract: In total gastrectomy for proximal gastric cancer that does not invade the greater curvature, splenectomy should be avoided as it increases operative morbidity without improving survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
240
3
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 272 publications
(254 citation statements)
references
References 22 publications
9
240
3
2
Order By: Relevance
“…The results of the JCOG0110 trial, which examined the importance of splenectomy in advanced primary gastric cancer, showed that splenectomy could be omitted if the lesion was not a greater curvature lesion [24]. We examined the influence of circumferential location of the tumor (Table S1 in the Electronic supplementary material, ESM).…”
Section: Discussionmentioning
confidence: 99%
“…The results of the JCOG0110 trial, which examined the importance of splenectomy in advanced primary gastric cancer, showed that splenectomy could be omitted if the lesion was not a greater curvature lesion [24]. We examined the influence of circumferential location of the tumor (Table S1 in the Electronic supplementary material, ESM).…”
Section: Discussionmentioning
confidence: 99%
“…was able to demonstrate the feasibility of carrying out para‐aortic dissection on top of D2 lymphadenectomy for gastric cancer, although there was no benefit to the 5‐year overall survival 24, 25. Most recently, Sano et al 26. showed that splenectomy for patients with proximal gastric cancer that does not involve the greater curvature was associated with increased morbidity without improving the overall 5‐year survival.…”
Section: Gastric Surgerymentioning
confidence: 99%
“…Long-term outcomes of this study have shown no survival benefit of splenectomy, but resulted in enhancing morbidity rate (15). Previous articles reported that morbidity rate of total gastrectomy with splenectomy, either by open surgery or LS, as 9.6-33.3% (16,17).…”
Section: Indications Of the Splenic Hilar Dissectionmentioning
confidence: 87%